Transcriptional Control of Metastasis by Integrated Stress Response Signaling - Lu, Si; Yang, Li-Xian; Cao, Zi-Jian; Zhao, Jiang-Sha; You, Jia; Feng, Yu-Xiong (Frontiers in Oncology, 2021)
As a central cellular program to sense and transduce stress signals, the integrated stress response (ISR) pathway has been implicated in cancer initiation and progression. Depending on the genetic mutation landscape, cellular context, and differentiation states, there are emerging pieces of evidence showing that blockage of the ISR can selectively and effectively shift the balance of cancer cells toward apoptosis, rendering the ISR a promising target in cancer therapy. Going beyond its pro-survival functions, the ISR can also influence metastasis, especially via proteostasis-independent mechanisms. In particular, ISR can modulate metastasis via transcriptional reprogramming, with the help of essential transcription factors. In this review, we summarized the current understandings of ISR in cancer metastasis from the perspective of transcriptional regulation.